Пользовательского поиска

+Jyz1tg(b)+Jxz1]sin(a)2}wz02+

+{(Jx1-Jz1)cos(2a)+[1-tg(b)4-2/cos(b)2]Jxz2cos(b)3

sin(2a)-[Jyz1tg(b)+2Jxz1]2sin(a)cos(a)-

-Jxy1tg(b)cos(2a)}wx0wz0+

+{[Jxy2sin(b)cos(b)(tg(b)2+1)+(Jx2-Jz2)]cos(a)}wx0wz2+

+{[Jxz2sin(b)cos(b)+Jxz2sin(b)3/cos(b)+Jyz2]cos(a)+

+[Jyz1cos(a)-Jxy1sin(a)]/cos(b)}wx0wy2-

-{[Jxz2sin(b)cos(b)(1+tg(b)2)+Jyz2]sin(a)+

+[Jyz1sin(a)+Jxy1cos(a)]/cos(b)}wz0wy2+

+{-[tg(b)2+1]sin(b)cos(b)Jxy2+(Jz2-Jx2)]sin(a)}wz0wz2+

+{[Jx2sin(b)cos(b)(1+tg(b)2)+Jy1tg(b)-(Jxy1+Jxy2)]

cos(a)-Jyz1sin(a)}wx0'+

+{[-Jx2sin(b)cos(b)(1+tg(b)2)+(Jxy1+Jxy2)-Jy1tg(b)]

sin(a)-Jyz1cos(a)}wz0'+

+{Jyz2sin(b)-Jxz2cos(b)}wz22-

-{Jxz2sin(b)+Jyz2cos(b)}wz2'+

+{(Jx2-Jy2)sin(b)+Jxy2cos(b)(tg(b)2-1)}wz2wy2+

+{Jx2sin(b)2/cos(b)-2Jxy2sin(b)+Jy2cos(b)+

+Jy1/cos(b)}wy2'

 

.

) Y1:

y1 = + = 8.1 + 1.65 = 9.75 ×

 

a = 0.776 .

b = 1.0 .

wy2 = -2 /.

wy2' = 3 /2.

wz2 = 2 /.

wz2' = -3 /2.

wx0 = wz0 = 1 /c.

wx0' = 0.2 /c2.

wz0' = - 0.2 /c2.

wy0 = 0.167 /c.

wy0' = 0.167 /c2.

 

:

 

= × 100 % = 16.9 %

 

 Rambler's Top100